Effects of sacubitril/valsartan on both metabolic parameters and insulin resistance in prediabetic non-obese patients with heart failure and reduced ejection fraction - Cloro, Cosima; Zaffina, Isabella; Sacchetta, Luca; Arturi, Federico; Clausi, Cristina; Lucà, Stefania; Pelle, Maria Chiara; Giofrè, Federica; Armentaro, Giuseppe; Forte, Valentina; De Rosa, Francesco Mario; Sciacqua, Angela; et al. (Frontiers in Endocrinology, 2022)
Background The effects of sacubitril/valsartan (sac/val) on metabolic parameters and insulin resistance (IR) in non-obese/prediabetic patients have not been previously described. Aim To evaluate the effects of sac/val on glycemic and metabolic parameters, Homeostatic Model Assessment of IR (HOMA-IR), and echocardiographic parameters in prediabetic patients with heart failure with reduced ejection fraction (HFrEF). Methods Fifty-nine patients with HFrEF (EF < 35%) but without obesity and/or type 2 diabetes mellitus have been enrolled. All the patients at baseline and week 24 underwent complete anthropometrical evaluation and were subjected to an echocardiogram test. IR has been assessed by HOMA-IR. Results After 24-week of treatment with sac/val, a significant reduction in fasting plasma glucose (109 ± 9 vs 103 ± 8 mg/dl, p < 0.0001), fasting plasma insulin (16 ± 4 vs 10 ± 4 UI/L), and hemoglobin A1c (HbA1c) value (6% ± 0.5% vs 5.3% ± 0.3%, p < 0.0001) was observed. Similarly, we observed a significant improvement in IR (HOMA-IR, 4.4 ± 0.9 vs 2.5 ± 0.6, p < 0.0001). The echocardiogram evaluation showed a significant reduction of the left ventricular end-diastolic volume (168 ± 24 vs 158 ± 22 ml, p < 0.05), a significant reduction of the left ventricular end-systolic volume (111 ± 26 vs 98 ± 22 ml, p < 0.005), and a significant reduction of E/e′ ratio. Sac/val use was also associated with an average 5.1% increase in ejection fraction. Conclusions Our data seem to indicate that sal/val enhances metabolic control and improves insulin resistance also in prediabetic non-obese patients with HFrEF.